Enhanced H2 evolution of TiO2 with efficient multiple electrons transfer modified by tiny CuOx–NiO bimetallic oxides. (26th April 2018) - Zhang, Meng; Sun, Runze; Long, Gaoyuan; Zhou, Chidong; Zhou, Yanfang; Chen, Mengxia; Huang, Xiuying; Han, Gaorui; Xu, Xinhua; Shi, Huixiang; Zhao, Weirong
Abstract: CuOx –NiO bimetallic oxides modified TiO2 catalysts were prepared via a precipitation-photoreduction approach for photocatalytic H2 production. 0.9%Cu0.1%Ni/TiO2 exhibited the highest H2 evolution rate (about 55.4 μmol/g/min) under UV–visible light irradiation (350–780 nm), which is higher than the sum of CuOx /TiO2 and NiO/TiO2 catalyst. Cu species exhibited more reducing valence state including Cu 0 when deposited on NiO/TiO2 compared with deposited on TiO2 . The polyvalent Cu species lead to enhanced photocurrent and reduced transfer resistance confirmed by photoelectron chemical analysis. CuOx –NiO modification of the TiO2 surface is beneficial for the photoexcited electron transfer, which suppresses electrons recombination. The lifetime of photoexcited electrons was enhanced greatly from 1.16 (TiO2 ) to 5.15 ns (CuOx –NiO/TiO2 ). A multiple electrons transfer mechanism for polyvalent bimetallic oxides co-modified TiO2 was proposed based on careful analysis. This work demonstrated a polyvalent bimetallic oxides modified TiO2 system with efficient photocatalytic H2 production which can provide some insightful understanding for bimetallic metal oxides co-catalyst design and H2 evolution mechanism. Highlights: CuOx –NiO/TiO2 exhibited 63-fold H2 evolution rate compared with that of pure TiO2 . The charge carriers lifetime increase from 1.16 (TiO2 ) to 5.15 ns (CuOx –NiO/TiO2 ). A multiple electron transfer mechanism over bimetal modified TiO2 was proposed.